Personality traits, mindfulness, and perceived stress in Chinese adults: a sequential explanatory mixed-methods approach - Zhao, Litang (Frontiers in Psychology, 2025)
BackgroundThis study explores how personality traits and mindfulness facets interact to influence perceived stress, focusing on a Chinese adult sample. It aims to address gaps in understanding the combined effects of dispositional and mindfulness factors on stress.MethodsA sequential explanatory mixed-methods design was employed. In the quantitative phase, 637 Chinese adults completed surveys measuring personality traits, mindfulness (attention, acceptance), and perceived stress. Hierarchical multiple regression, moderation, and mediation analyses were conducted. In the qualitative phase, semi-structured interviews with selected participants provided deeper insights into the quantitative findings.ResultsNeuroticism (β = 0.29, p < 0.001) and conscientiousness (β = 0.15, p < 0.01) were positively associated with perceived stress, while mindfulness-acceptance (β = −0.25, p < 0.001) was a significant negative predictor. Neuroticism and mindfulness-acceptance uniquely explained 8 and 6% of the variance in stress, respectively. Mindfulness-attention moderated the relationship between agreeableness and stress, amplifying agreeableness’ stress-buffering effect in individuals with low mindfulness-attention. Mediation analysis revealed mindfulness-acceptance partially mediated the agreeableness-stress link. Qualitative interviews underscored the role of personality and mindfulness in shaping stress responses and coping mechanisms.ConclusionThe findings highlight mindfulness-acceptance as a critical factor in reducing stress, particularly in individuals with agreeable personalities. These results support the development of mindfulness-based interventions targeting acceptance to enhance stress resilience across diverse personality profiles.